2013
DOI: 10.1111/1440-1681.12041
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte membrane transporters during human ageing: Modulatory role of tea catechins

Abstract: Ageing is associated with many physiological and cellular changes, many of which are due to alterations in the plasma membrane. The functions of membrane transporter proteins are crucial for the maintenance of ionic homeostasis between the extra- and intracellular environments. The aim of the present study was to determine the status of erythrocyte membrane transporters, specifically Ca(2+) -ATPases, Na(+) /K(+) -ATPases and the Na(+) /H(+) exchanger (NHE), during ageing in humans. Furthermore, because tea cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…However, it has to be mentioned that data concerning aging are controversial. Some other studies have shown that in healthy individuals, the enzyme activity was not influenced by aging [ 48 , 49 , 69 ].…”
Section: Erythrocyte Nak-atpase and Deformability In Various Patho/physiological Situationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has to be mentioned that data concerning aging are controversial. Some other studies have shown that in healthy individuals, the enzyme activity was not influenced by aging [ 48 , 49 , 69 ].…”
Section: Erythrocyte Nak-atpase and Deformability In Various Patho/physiological Situationsmentioning
confidence: 99%
“…A study of erythrocytes from normal healthy subjects differing in age, showed that the above-mentioned tea catechin (EGCG) decreased the oxidation of membrane lipids throughout the range of human age with the highest effectivity in the group of oldest individuals [ 96 , 97 ]. Concerning the ionic homeostasis in erythrocytes, EGCG also mitigated most effectively the changes induced by t-BHP on Na,K-ATPase enzyme in all age groups; however, the effect was again more pronounced in the oldest age group [ 69 ]. A different study of elevated free radical formation induced by an increase in oxygen partial pressure (using in vitro hyperbaric oxygen model for erythrocytes from healthy volunteers) showed that EGCG effectively ameliorated hemorheological abnormality and enhanced erythrocyte deformability [ 98 ].…”
Section: Protection Of Erythrocyte Nak-atpase and Deformability By Nutritional Antioxidantsmentioning
confidence: 99%
“…The aim of this study was to investigate the effects of acute physical exercise on the oxidative stress process in the erythrocytes of young sedentary healthy male subjects. Taking into account that the redox balance in ageing cells is disturbed in favour of the oxidation processes (Pandey, ), we examined whether the age of the erythrocytes has an effect on the changes resulting from oxidative stress induced by exhaustive exercise. Oxidative stress markers, such as protein thiol groups and lipid peroxidation products, were measured and compared.…”
Section: Introductionmentioning
confidence: 99%
“…Mutation in the activity of membrane transport systems has been reported in various pathological conditions including diabetes, cancer, neurodisorders, CVD, and aging [ 10 13 ]. Impairment in transporters activity and deregulation of ions-homeostasis has been linked with membrane fluidity and susceptibility of membrane toward oxidative damage [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%